Majority of German citizens, US citizens and climate scientists support policy advocacy by climate researchers and expect greater political engagement. (21st January 2021) - Cologna, Viktoria; Knutti, Reto; Oreskes, Naomi; Siegrist, Michael
Abstract: Scientists' role in outreach and advocacy has been debated extensively, but empirical evidence on its perceived legitimacy is scarce. We contacted scientists researching climate change to investigate scientists' engagement levels, as well as expectations regarding political and public engagement. We then compared how scientists ( N = 1107) and German and US citizens ( N = 884) view scientists' engagement and how scientists' advocacy affects their credibility. We find that perceptions differ across countries, with scientists perceiving more strongly than the public that scientists should politically and publicly engage. However, the public agrees that scientists should engage, and that they should increase these efforts. The majority of citizens agrees that scientists should advocate for climate-related policies and work closely with policymakers but refrain from endorsing climate protests. Further, openly supporting climate policies does not adversely affect scientists' perceived trustworthiness or honesty, while it negatively affects perceptions of scientists' objectivity. Our study provides empirical evidence that can help climate change researchers to better understand the public's demand for, and perceived legitimacy of, different engagement activities.